Intrinsic heterogeneity in axon regeneration. (16th December 2022) - Fu, Xiu-Qing; Zhan, Wen-Rong; Tian, Wei-Ya; Cao, Dong-Dong; Luo, Zhen-Ge
Abstract : The nervous system is composed of a variety of neurons and glial cells with different morphology and functions. In the mammalian peripheral nervous system (PNS) or the lower vertebrate central nervous system (CNS), most neurons can regenerate extensively after axotomy, while the neurons in the mammalian CNS possess only limited regenerative ability. This heterogeneity is common within and across species. The studies about the transcriptomes after nerve injury in different animal models have revealed a series of molecular and cellular events that occurred in neurons after axotomy. However, responses of various types of neurons located in different positions of individuals were different remarkably. Thus, researchers aim to find the key factors that are conducive to regeneration, so as to provide the molecular basis for solving the regeneration difficulties after CNS injury. Here we review the heterogeneity of axonal regeneration among different cell subtypes in different animal models or the same organ, emphasizing the importance of comparative studies within and across species.